Examination of Athlete Triad Symptoms Among Endurance-Trained Male Athletes: A Field Study - Moore, Erin M.; Drenowatz, Clemens; Stodden, David F.; Pritchett, Kelly; Brodrick, Thaddus C.; Williams, Brittany T.; Goins, Justin M.; Torres-McGehee, Toni M. (Frontiers in Nutrition, 2021)
Abstract Background: Studies examining the physiological consequences associated with deficits in energy availability (EA) for male athletes is sparse. Purpose: To examine Male Athlete Triad components; low energy availability (LEA) with or without an eating disorder risk (ED), reproductive hormone (testosterone [T]), and bone mineral density (BMD) in endurance-trained male athletes during different training periods. Methods: A cross-sectional design with 14 participants (age: 26.4  4.2 yrs.; weight: 70.6  6.4 kg; height: 179.5  4.3 cm, BMI: 21.9  1.8 kg/m2) were recruited from the local community. Two separate training weeks (low [LV] and high [HV] training volumes) were used to collect the following: 7-day dietary and exercise logs, and blood concentration of T. Anthropometric measurements were taken prior to data collection. A one-time BMD measure (after the training weeks) and VO2max-HR regressions were utilized to calculate EEE. Results: Overall, EA presented as 27.6  10.7 kcal/kgFFM·d-1 with 35% (n=5) of participants demonstrating increased risk for ED. Examining Male Triad components, 64.3% presented with LEA (≤ 30 kcal/kgFFM·d-1) while participants presented with T (1780.6  1672.6 ng/dL) and BMD (1.31  0.09 g/cm2) within normal reference ranges. No differences were found across the 2 training weeks for EI, with slight differences for EA and EEE. Twenty-five participants (89.3%) under-ingested CHO across both weeks, with no differences between weeks. Conclusion: Majority of endurance-trained male athletes presented with one compromised component of the Triad (LEA with or without ED risk) however long-term negative effects on T and BMD were not demonstrated. Over 60% of participants presented with an EA 30 kcal/kgFFM·d-1 along with almost 90% not meeting CHO needs. These results suggest male endurance-trained athletes may be at risk to negative health outcomes similar to mechanistic behaviors related to EA with or without ED in female athletes.